Computational mapping analysis of artificial intelligence in education publications: A bibliometric approach utilizing vosviewer - Fanny Rahmatina Rahim; Ari Widodo (Universitas PGRI Kanjuruhan Malang, 2024)
In recent years, interest in the application of AI in education has increased significantly. However, there has been no research explaining the research trends in this area through bibliometric analysis. The goal of this study was to undertake a bibliometric analysis to look at how research on artificial intelligence (AI) in education has evolved. This study used open access bibliometric software for conducting exploratory research and discovering new research directions. It focuses on VOSviewer, a freely available software tool designed to analyze and visualize bibliometric relationships across various variables. Starting with existing examples, the paper then presents an original case study utilizing bibliometrics to investigate the impact of AI on education. Using Scopus data and VOSviewer, this case study analyzes and compares co-occurrence patterns among publications over a decade, showcasing how such software can effectively support preliminary investigations and influence more formal research endeavors.